Implementation of the EU environmental law in the context of cross-border damage to marine environment: case study of the Baltic Sea - Jansone, Karlīna (Riga Graduate School of Law, 2018)
The purpose of the thesis is to analyse the applicability and implementation of the European Union (EU) environmental law to cross-border damage to the marine environment, also assessing their applicability to the Baltic Sea as well as progress on implementation, and additionally to review the relationship between the EU law and HELCOM – intergovernmental body responsible for carrying out the obligations under the Helsinki Convention on the Protection of the Marine Environment of the Baltic Sea.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law